A Comparison of the Tourist Potential of the Climates of the Coastal Resort at Odesa and the Inland Resort by Lake Svityaz - Olga Shevchenko; Sergiy Snizhko; Oleg Gryniuk; Andreas Matzarakis (Atmosphere, 2023)
The aim of this study is to evaluate and compare the human-biometeorological conditions at two resorts in Ukraine: a coastal resort located at Odesa in southern Ukraine and an inland resort situated by the lake at Svityaz situated in northwest Ukraine. The results of this study can facilitate the assessment of the tourist potentials of both locations by the tourism industry, tour operators, and tourists. The evaluation is based on an analysis of the Physiologically Equivalent Temperature (PET) and parameters presented through the Climate–Tourism/Transfer–Information Scheme (CTIS) for the period 1991–2020. The CTIS data reveal that better conditions in terms of thermal comfort can be found during the warm period from May to September at both sites. The results show that the highest frequency of all grades of heat stress are observed in the last 10-day period of July and in the first 10-day period of August at both stations, but at Odesa, the frequency of heat stress of any grade is approximately 10% higher than at Svityaz. The frequency of moderate, strong and extreme heat stress during the daytime in July and in the first two 10-day periods of August at Odesa ranged from 51.3% to 66.5%, and at Svityaz it ranged between 40.2 and 54.6%. Human-biometeorological conditions during heat waves are more strenuous at Odesa. The frequency of days with extreme heat stress at 12 UTC during summer heat waves is 48.4% at Odesa and 35.6% at Svityaz. The results show a higher frequency of thermal stress at Odesa, which makes this resort less comfortable for people vulnerable to heat stress.